A geometallurgical study of flotation performance in supergene and hypogene zones of Sungun copper deposit. Issue 2 (3rd April 2021) - Bahrami, Ataallah; Ghorbani, Yosef; Sharif, Jafar Abdollahi; Kazemi, Fatemeh; Abdollahi, Morteza; Salahshur, Abbas; Danesh, Abolfazl
ABSTRACT: The feed of mineral processing plants, usually consist of different minerals from various geological zones, which show different behavior in separation processes. In this research, samples from supergene and hypogene zones were provided to investigate the flotation behavior of copper minerals. Flotation experiments were carried out in three phases of supergene sample, hypogene sample and mixed samples. Based on the results, the recovery rate of the mixed sample was 83.61%, which is 7.63% and 1.79% higher than the recovery of the samples of hypogene and supergene zones, respectively. The concentrate grade values obtained for blended, hypogene zone and supergene zone are 10.32%, 2.81% and 12.37%, respectively. The maximum values of flotation constant and infinite recovery are 0.956 (s −1 ) and 88.833% for the mixed sample. It was also concluded that the highest amount of k and infinitive recovery were related to supergene zone sulfide flotation which are 0.831 (s −1 ) and 84.33% respectively.